Cognitive Training Sustainably Improves Executive Functioning in Middle-Aged Industry Workers Assessed by Task Switching: A Randomized Controlled ERP Study - Gajewski, Patrick D.; Freude, Gabriele; Falkenstein, Michael (Frontiers in Human Neuroscience, 2017)
Recently, we reported results of a cross-sectional study investigating executive functions in dependence of aging and type of work. That study showed deficits in performance and electrophysiological activity in middle aged workers with long-term repetitive and unchallenging work. Based on these findings we conducted a longitudinal study that aimed at ameliorating these cognitive deficits by means of a trainer-guided cognitive training in 57 further middle aged workers with repetitive type of work from the same factory. This study was designed as a randomized controlled trail with pre- (t1), post- (t2), and a three month follow-up (t3) measure. The waiting control group was trained between t2 and t3. The training lasted 3 months (20 sessions) and was evaluated with the same task switching paradigm used in the previous cross-sectional study. The cognitive training improved performance in accuracy at the behavioral level and affected the electrophysiological correlates of retrieval of stimulus-response sets (P2), response selection (N2), and error detection (Ne), thus unveiling the neuronal background of the behavioral effects. The same training effects were observed in the waiting control group after cognitive training at t3. Moreover, at t3, most of the behavioral and electrophysiological training-induced changes were found stable. Hence, cognitive training appears to be an important intervention for compensating cognitive deficits in executive functions in middle aged employees with cognitively unchallenging work.